![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\frac{\sqrt{x}-5}{\sqrt{x}+3}\)
\(A=-1\Leftrightarrow\frac{\sqrt{x}-5}{\sqrt{x}+3}=-1\)
\(\Leftrightarrow\sqrt{x}-5=-\sqrt{x}-3\)
\(\Leftrightarrow2\sqrt{x}=2\)
\(\Leftrightarrow\sqrt{x}=1\Leftrightarrow x=1\)
:>
\(A=\frac{\sqrt{x}-5}{\sqrt{x}+3}\)
\(A=-1\)
\(\Leftrightarrow\frac{\sqrt{x}-5}{\sqrt{x}+3}=-1\)
\(\Leftrightarrow\sqrt{x}-5=-\sqrt{x}-3\)
\(\Leftrightarrow2\sqrt{x}=2\)
\(\Leftrightarrow\sqrt{x}=1\)
\(\Leftrightarrow x=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)Tại \(x=\frac{16}{9}\) ta có: \(A=\frac{\sqrt{x}+1}{\sqrt{x}-1}=\frac{\sqrt{\frac{16}{9}}+1}{\sqrt{\frac{16}{9}}-1}=\frac{\frac{4}{3}+1}{\frac{4}{3}-1}=\frac{\frac{7}{3}}{\frac{1}{3}}=7\)
Tại \(x=\frac{25}{9}\) ta có: \(A=\frac{\sqrt{x}+1}{\sqrt{x}-1}=\frac{\sqrt{\frac{25}{9}}+1}{\sqrt{\frac{25}{9}}-1}=\frac{\frac{5}{3}+1}{\frac{5}{3}-1}=\frac{\frac{8}{3}}{\frac{2}{3}}=4\)
b)Khi \(A=5\Rightarrow\frac{\sqrt{x}+1}{\sqrt{x}-1}=5\)(*)
Đk:\(\sqrt{x}-1\ne0\Rightarrow x\ne1;\sqrt{x}\ge0\Rightarrow x\ge0\)
Đặt \(\sqrt{x}+1=t\left(t\ge0\right)\),(*) trở thành
\(\frac{t}{t-2}=5\Rightarrow t=5\left(t-2\right)\)
\(\Rightarrow t=5t-10\)
\(\Rightarrow2t=5\Rightarrow t=\frac{5}{2}\)(thỏa mãn)
\(t=\frac{5}{2}\Rightarrow\sqrt{x}+1=\frac{5}{2}\)
\(\Rightarrow\sqrt{x}=\frac{3}{2}\Leftrightarrow\sqrt{x^2}=\left(\frac{3}{2}\right)^2\Leftrightarrow x=\frac{9}{4}\)(thỏa mãn)
Vậy \(x=\frac{9}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Thay \(x=\frac{16}{9}\) vào biểu thức ta có:
\(A=\frac{\sqrt{\frac{16}{9}}+1}{\sqrt{\frac{16}{9}}-1}=\frac{\frac{4}{3}+1}{\frac{4}{3}-1}=\frac{\frac{7}{3}}{\frac{1}{3}}=7\)
Vậy \(A=7\)
Thay \(x=\frac{25}{9}\) vào biểu thức ta có:
\(A=\frac{\sqrt{\frac{25}{9}}+1}{\sqrt{\frac{25}{9}}-1}=\frac{\frac{5}{3}+1}{\frac{5}{3}-1}=\frac{\frac{8}{3}}{\frac{2}{3}}=4\)
Vậy \(A=4\)
\(S=\frac{\sqrt{x}+1}{\sqrt{x}-1}\)( ĐKXĐ : \(\hept{\begin{cases}x\ge0\\x\ne1\end{cases}}\))
Để S = 5 thì \(\frac{\sqrt{x}+1}{\sqrt{x}-1}=5\)
=> \(\sqrt{x}+1=5\sqrt{x}-5\)
<=> \(5\sqrt{x}-5-\sqrt{x}-1=0\)
<=> \(4\sqrt{x}-6=0\)
<=> \(\sqrt{x}=\frac{3}{2}\)
<=> \(x=\frac{9}{4}\)( tm )
Vậy với x = 9/4 thì S = 5
<=> \(4\sqrt{x}=6\)